Evaluation of caries-associated virulence of biofilms from Candida albicans isolated from saliva of pediatric patients with sickle-cell anemia - Brighenti, Fernanda Lourenção [UNESP]; Medeiros, Amanda Coelho; Matos, Bruno Mello; Ribeiro, Zulene Eveline Abreu; Koga-ito, Cristiane Yumi (Faculdade De Odontologia De Bauru - USP, 2014)
A previous study demonstrated that the amount of Candida spp. in saliva is higher in children with sickle-cell disease. The results from a recent study demonstrate its participation in the etiology of dental caries. Objective This study assessed caries-associated virulence (production of acid, extracellular polysaccharides, proteins and metabolic activity) of biofilms from Candida albicans isolated from saliva of patients with sickle-cell anemia in comparison to isolates obtained from matched healthy children. Material and Methods The isolates were previously obtained from 25 children (4-6 years) and their matched controls (healthy children). One isolate of C. albicans per children was used, totaling 25 isolates per group. The C. albicans biofilms were grown for five days and analyzed regarding the production of lactic acid, extracellular polysaccharides, proteins and metabolic activity. The production of lactic acid was determined by the enzymatic method. The concentration of extracellular polysaccharides was determined by the phenol-sulphuric acid method, and the concentration of the protein was analyzed using the QuantiPro BCA kit. The XTT reduction was used to verify the metabolic activity. The data were analyzed with GraphPad Prism at 5%. Results The Mean±standard deviation for acid production, extracellular polysaccharides, proteins and metabolic activity of isolates from sickle-cell group was, respectively: 7.1±5.0 mmol/L; 15.6±2.5 μg glucose/mg biofilm; 7,503±3,097 μg/mL; A490 3.5±0.7. For isolates from control group the values obtained were: 3.5±3.3 mmol/L; 12.8±3.4 μg glucose/mg biofilm; 4,995±682 μg/mL; A490 3.4±0.5. The C. albicans isolates from patients with sickle-cell anemia produced a significantly greater quantity of acids (p=0.025), polysaccharides (p=0.025) and proteins (p=0.047) compared with the isolates from control group. However, there was no difference in metabolic activity (XTT) between groups (p=0.750). Conclusion The C. albicans biofilms from patients with sickle-cell anemia presented a greater caries-associated virulence than isolates from healthy children.
Keywords: Sickle cell anemia; Biofilms; Candida spp; Dental caries